2017
DOI: 10.4025/revcivet.v3i2.34435
|View full text |Cite
|
Sign up to set email alerts
|

RESISTÊNCIA AOS ANTIMICROBIANOS EM Staphylococcus spp. ASSOCIADOS À MASTITE BOVINA

Abstract: A mastite é a principal afecção do gado leiteiro brasileiro, constituindo um fator limitante na produtividade das propriedades rurais. A mastite é causada principalmente por bactérias e consiste em um processo infeccioso e inflamatório da glândula mamária, acarretando em modificação da composição do leite in natura com aumento da contagem de células somáticas. A adoção de boas práticas para uma ordenha higiênica é apontado como método eficaz e de baixo custo para o controle e prevenção da mastite. No entanto, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…Mastitis is a frequent cause of economic losses in dairy cows, compromising animal health, milk composition and public health. The incorrect and indiscriminate antimicrobial use in animals has selected multiresistant bacteria (Moritz and Moritz, 2016), as evidenced for Staphylococcus spp. strains isolated from cows (Liu et al., 2017; Unakal and Kaliwal, 2010; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis is a frequent cause of economic losses in dairy cows, compromising animal health, milk composition and public health. The incorrect and indiscriminate antimicrobial use in animals has selected multiresistant bacteria (Moritz and Moritz, 2016), as evidenced for Staphylococcus spp. strains isolated from cows (Liu et al., 2017; Unakal and Kaliwal, 2010; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(Silva et al, 2013). Um método eficaz e de baixo custo para o controle e prevenção da mastite é o uso de boas práticas durante a ordenha, entretanto, na conduta terapêutica é importante a identificação do patógeno e o monitoramento da resistência aos antimicrobianos nos casos de mastite subclínica (Moritz;Moritz 2016).…”
Section: Introductionunclassified
“…O uso inadequado e indiscriminado de antimicrobianos tem promovido a ocorrência de cepas resistentes, prejudicando a eficiência do tratamento, tornando-se um problema de saúde humana e animal (Mendonça et al, 2012); Moritz;Moritz (2016). Diversos microrganismos patogênicos podem causar inflamação no teto do animal, entretanto Staphylococcus aureus (S. aureus) é um dos principais agentes etiológicos causadores da mastite bovina (Silva et al, 2013;Song et al, 2016;Sheet et al, 2019).…”
Section: Introductionunclassified
“…Mastitis treatment and prevention consists mainly of the use of antibiotics and proper animal handling to prevent the spread of the disease to healthy animals. However, the use of antibiotics requires caution in order to avoid the emergence of resistant bacteria (Costa et al, ; Moritz & Moritz, ). Krewer et al () found simultaneous resistance to three or more antibiotics in 65.6% of Staphylococcus isolates that cause mastitis.…”
Section: Introductionmentioning
confidence: 99%